Management Audit to Assess The Effectiveness of Human Resources Functions at PT Kimia Farma Plant Semarang - Astisa, Fasya Putri; Karyanti, Tutik Dwi; Arbainah, Siti (Applied Accounting and Management Review (AAMAR), 2025)
Abstract: This study aims to analyze the effectiveness of 11 (eleven) human resource functions at PT Kimia Farma Plant Semarang. This research is a qualitative descriptive study, conducted through the distribution of questionnaires using a saturated sampling technique. Data collection techniques included interviews, questionnaires, documentation, and observation. Data analysis was conducted using management audit with four stages: preliminary audit, review and testing of management controls, detailed audit, and reporting. The results of the study indicate that the company has implemented all 11 (eleven) HR functions, which include HR planning, recruitment, selection, training and development, career development, performance appraisal, reward and compensation, employee protection, labor relations, and termination of employment (PHK). Of these functions, eight were deemed effective: HR planning, HR recruitment, HR selection, career planning and development, performance appraisal, reward and compensation systems, employee protection, labor relations, and termination of employment (PHK). Meanwhile, three other functions have not been implemented effectively, namely HR orientation and placement, training and development, and performance evaluation.